Hubungan antara Career Capital dan Work-Life Balance pada Karyawan di PT. Petrokimia Gresik - Ula, Ilma Iftahul; Susilawati, Ikra Rahma; Widyasari, Selly Dian (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2015)
This study aimed to examine the correlation between career capital and worklife balance towards the employees of PT Petrokimia Gresik. The total sample was 102 official employees in the office of PT Petrokimia Gresik. Data were collected using simple random sampling technique; the career capital scale was based on Arthur and Inkson theory (2001), while the work-life balance scale was transadapted from Fisher's theory (2009). The itemtotal correlation coefficient was calculated using Product Moment Pearson and the reliability was examined using internal consistency technique. The result showed the Product Moment correlation (r) was 0,522 with p = 0,000, showing the positive linear correlation was at medium range between the two variables. This means, the higher the career capital of the employees, the higher their work-life balance. Otherwise, the lower career capital of the employees, the lower their work-life balance.